1999
DOI: 10.1073/pnas.96.25.14594
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-induced membrane displacement in patch pipettes activates mechanosensitive channels

Abstract: The patch-clamp technique allows currents to be recorded through single ion channels in patches of cell membrane in the tips of glass pipettes. When recording, voltage is typically applied across the membrane patch to drive ions through open channels and to probe the voltage-sensitivity of channel activity. In this study, we used video microscopy and single-channel recording to show that prolonged depolarization of a membrane patch in borosilicate pipettes results in delayed slow displacement of the membrane i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…This general form of bimolecular material system can be considered a smart material due to the stimuli-responsive properties of the network. Through previous work and our research it has been demonstrated that such a network can be made responsive to the application of a wide range of external stimuli, such as mechanical stress [37,38], optical inputs [27], and thermal inputs [39,40]. Likewise, it has been demonstrated that the control of collective transport across artificial membranes can produce a macroscopic pumping action and material swelling that mimics the properties of certain plant models [28,35].…”
Section: Biomolecular Materials Systemsmentioning
confidence: 69%
“…This general form of bimolecular material system can be considered a smart material due to the stimuli-responsive properties of the network. Through previous work and our research it has been demonstrated that such a network can be made responsive to the application of a wide range of external stimuli, such as mechanical stress [37,38], optical inputs [27], and thermal inputs [39,40]. Likewise, it has been demonstrated that the control of collective transport across artificial membranes can produce a macroscopic pumping action and material swelling that mimics the properties of certain plant models [28,35].…”
Section: Biomolecular Materials Systemsmentioning
confidence: 69%
“…This behaviour is similar to that observed previously in myotubes (Franco‐Obregon & Lansman, 2002), where resting MSC activity increased in mdx patches over a period of several minutes, while in wild‐type patches it decreased. Resting MSC activity in mdx patches was also sensitive to previous suction and pressure stimulation (Franco‐Obregon & Lansman, 2002) and depolariziation (Gil et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…An Axopatch 200A amplifier, Digidata 1322A, and Clampex 9.0 software (Molecular Devices, Sunnyvale, CA, USA) were used for voltage‐clamp and data acquisition. Previous work showed that large transmembrane voltages (100+ mV) applied over seconds produced patch creep, which caused activation of mechanosensitive channels in Xenopus oocytes (Gil et al 1999). To prevent this creep, we kept the holding potential at 0 mV.…”
Section: Methodsmentioning
confidence: 99%